Potpourri recycled paper collections - Arenas, Arlene Joy I.; Aguilar, Romelo; Bagaforo, Marie Cris.; Benedicto, Patricia; Borra, Dee Jay.; Colon, Mary Gem.; Cordova, Stephanie; Delgado, Romella; Garmay, Rutchel; Gonzales, Venus; Pahunao, Emee Rose.; Sanson, Kathleen (2001.)
Executive summary - The group, in making the business plan, aims to fulfill a part of the requirement of the course in Management 138. It also aims at bridging the gap between theory and reality by having to undergo the rigid process of putting up a small business and convincing a representative of a financial institution in granting the group enough loans for capitalization. Potpourri's mission is "to be the island's leading manufacturer of recycled paper products." To create awareness for the need to preserve mother earth while being profitable. The company aims for efficiency and social responsibility. potpourri, together with its committed workers aims for nothing but the best value for customers because potpourri believes that its strength rest on its continuing pursuit of excellenece. Each member has his own part to play and is in himself an asset to the company. The marketing department is directly responsible for the understanding of customers current needs and wants while the eproduction department is in charge of keeping cost of production to its minimum. The relatively small size of the company and the simplicity of its structure bring in a more personal and cooperative relationship among members. As a form of strategic alliance, a good supplier relation is being maintained so as to be sure of a good deal and top quality raw materials.
Business Plan (Mgt 138 - Enterprise Planning) -- Iloilo City : University of the Philippines in the Visayas-College of Management, March 30, 2001.